Occupational Sorting of School Graduates: The Role of Economic Preferences - Didier Fouarge; Ben Kriechel; Thomas Dohmen (Institute for the Study of Labor (IZA), 2014)
We relate risk attitudes and patience of young graduates from high-school, college and university, measured around the time that they start their labor market career in a large representative survey, to the riskiness and timing of earnings in the occupations they choose to work in. We find a systematic positive and significant relation between willingness to take risks and measures of occupational earnings risks and employment risk that we derive from a large administrative data set. Patient individuals are significantly more likely to choose for occupations with a steep earnings profile. Individuals whose economic preferences are not well aligned with the riskiness and timing of earnings in their initial occupation are more likely to change to an occupation that better matches their economic preferences.
Keywords: J24; J31; D01; 330; risk preferences; earnings risk; sorting; occupational choice